Coordinating primary care services: A case of policy layering. Issue 2 (February 2019) - Rudoler, David; Peckham, Allie; Grudniewicz, Agnes; Marchildon, Greg
Highlights: Policy change can occur through processes of incremental policy layering. Policy layering can result in unintended consequences. We propose principles of 'smart layering' to guide decision-makers. This approach is applied to reform of primary health care systems. Abstract: In this paper, we discuss the processes of policy layering as they relate to health care reform. We focus on efforts to achieve systems of coordinated primary care, and demonstrate that material change can be achieved through processes of incremental policy layering. Such processes also have a high potential for unintended consequences. Thus, we propose new principles of 'smart' policy layering to guide decision-makers to do incrementalism better. We then apply these principles to recent primary care reforms in Ontario, Canada. This paper conceptualizes 'smart' policy layering as a mechanism to achieve productive policy change in contexts with strong institutional barriers to reform.